MOTIVATIONAL READINESS OF UNDERGRADUATE STUDENTS IN PEDAGOGICAL SPHERE TO WORK WITH CHILDREN WITH SPECIAL EDUCATIONAL NEEDS - Roksolyana Vasylivna OLIINYK; Inna Romanivna PEREPELIUK (Association of Social and Educational Innovation, 2022)
The article is devoted to the theoretical and practical analysis of the future preschool teachers' readiness to work with children with special educational problems. The effectiveness of inclusive education depends largely on the desire and willingness of the undergraduate students, and in the future teachers to strong performance with all participants in the educational process i.e. in particular with parents, educators, developmental paediatrician, speech and language pathologist, doctors and others. This readiness is determined by the specific conditions of the future teacher professional activity and is based on the number of competencies formation such as: academic, social and personal, professional, cultural. The most important component of such readiness is motivational readiness, as the knowledge, skills, and abilities can be acquired during the activity process, and only when there is motivation to work with special children. The paper also analyses the scientists' works who dealt with the problems of motivation and teachers motivational readiness in general. The motivational readiness basic components of the pedagogical area undergraduate students to work in the conditions of inclusion according to the required state standard are identified and described. The leading role of motivational factors to disclose the creative potential and self-development of future preschool teachers is revealed. The article has analysed that the meaningful content of the "inclusion", "children with special educational problems", "motivational readiness", "inclusive educational environment" concepts has advantages and disadvantages that change according to different stages of society formation and development.